2021
DOI: 10.1039/d1lc00469g
|View full text |Cite
|
Sign up to set email alerts
|

Are droplets really suitable for single-cell analysis? A case study on yeast in droplets

Abstract: Single-cell analysis has become one of the main cornerstones of biotechnology, inspiring the advent of various microfluidic compartments for cell cultivation such as microwells, microtrappers, microcapillaries, and droplets. A fundamental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…We see that cells grew more in the swollen and diluted DE droplets than in nonswollen droplets with standard media. This contradicts the flask results, although it is in agreement with other studies showing that the cell growth phase was delayed in smaller microfluidic droplets in comparison with larger droplets. Our enhanced growth in swollen cores may be because the accumulation of biological waste products in smaller cores reduces growth more strongly than a lack of nutrients or nonideal salinity does in the swollen cores. Clearly, droplet-based cell cultivation requires extra consideration over bulk cultures.…”
Section: Resultssupporting
confidence: 81%
“…We see that cells grew more in the swollen and diluted DE droplets than in nonswollen droplets with standard media. This contradicts the flask results, although it is in agreement with other studies showing that the cell growth phase was delayed in smaller microfluidic droplets in comparison with larger droplets. Our enhanced growth in swollen cores may be because the accumulation of biological waste products in smaller cores reduces growth more strongly than a lack of nutrients or nonideal salinity does in the swollen cores. Clearly, droplet-based cell cultivation requires extra consideration over bulk cultures.…”
Section: Resultssupporting
confidence: 81%
“…As a result, selected cells may not behave the same way when scaled up for real-world applications as they did when cultured within these nanoliter-sized compartments. This behavior has been recently observed for yeast cells, where the size of the droplet affects overall cell morphology following culture ( 14 ). Scientists often need to perform further experiments and do additional genetic manipulation of selected strains to adapt them to scaled-up industrial cultures, a process that can take several months or years without guaranteed success.…”
supporting
confidence: 62%
“…Previous studies demonstrated that droplet size affects the division of cells in microfluidic droplets surrounded by oil ( 31 , 32 ). Another recent study has demonstrated that yeast cells cultured in large flasks, large droplets, and small droplets differed morphologically ( 14 ). There may be several reasons for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we can employ various machine learning approaches to recognize, predict, understand, and obtain data/knowledge. In this way, parametric approaches can be applied in the future to perform correlation analyses to compare morphologies [ 28 ], classification analyses to distinguish categories based on morphology [ 29 ], prediction analyses to identify similar morphologies [ 30 ], factor analyses to explore potential common factors [ 31 ], analysis of morphological diversity for breeding purposes [ 32 , 33 ], and analysis of sources of bias in microfluidic cell culture research [ 34 ].…”
Section: Discussionmentioning
confidence: 99%